Anion Effect of Zinc Source on Chemically Deposited ZnS(O, OH) Films. (9th February 2010) - Ernits, K.; Muska, K.; Danilson, M.; Raudoja, J.; Varema, T.; Volobujeva, O.; Altosaar, M.
Abstract : The study on the anion effect of different Zn sources—Zn( CH 3 COO ) 2, ZnCl 2, ZnI 2, Zn( NO 3 ) 2 and ZnSO 4 —on the chemical deposition of ZnS(O, OH) films revealed that the growth rate and composition of the ZnS(O, OH) layer depend on the instability constant (pK) value of the corresponding Zn-complex Zn( L ) n in the chemical bath solution. In the region ofpK Zn ( NH 3 ) 2 + > pK Zn ( L ) n the ZnS(O, OH) film's growth rate and ZnS concentration in films increased with the increasing pK value of the used Zn salt complex up to the pK value of theZn [ NH 3 ] 2 + complex and decreased in the region wherepK Zn ( NH 3 ) 2 + < pK Zn ( L ) n . The band gap values (around 3.6 eV in most cases) of deposited ZnS(O, OH) films did not depend on the Zn precursor's instability constant, the ZnS(O, OH) film from zinc nitrate containing bath has higher band gap energy (E g = 3.8 eV). The maximum efficiency of CISSe and CZTSSe monograin layer solar cells was gained with ZnS(O, OH) buffer layer deposited from CBD solution containing Zn( CH 3 COO ) 2 as Zn source, which provided the highest growth rate and ZnS concentration in the ZnS(O, OH) film on glass substrates.